Cinnamomum cassia exhibits antileishmanial activity against Leishmania donovani infection in vitro and in vivo. - Farhat Afrin; Garima Chouhan; Mohammad Islamuddin; Muzamil Y Want; Hani A Ozbak; Hassan A Hemeg (Public Library of Science (PLoS), 2019)
Background There is a pressing need for drug discovery against visceral leishmaniasis, a life-threatening protozoal infection, as the available chemotherapy is antiquated and not bereft of side effects. Plants as alternate drug resources has rewarded mankind in the past and aimed in this direction, we investigated the antileishmanial potential of Cinnamomum cassia. Methodology Dichloromethane, ethanolic and aqueous fractions of C. cassia bark, prepared by sequential extraction, were appraised for their anti-promastigote activity along with apoptosis-inducing potential. The most potent, C. cassia dichloromethane fraction (CBD) was evaluated for anti-amastigote efficacy in infected macrophages and nitric oxide (NO) production studied. The in vivo antileishmanial efficacy was assessed in L. donovani infected BALB/c mice and hamsters and various correlates of host protective immunity ascertained. Toxicity profile of CBD was investigated in vitro against peritoneal macrophages and in vivo via alterations in liver and kidney functions. The plant secondary metabolites present in CBD were identified by gas chromatography-mass spectroscopy (GC-MS). Principal findings CBD displayed significant anti-promastigote activity with 50% inhibitory concentration (IC50) of 33.6 μg ml-1 that was mediated via apoptosis. This was evidenced by mitochondrial membrane depolarization, increased proportion of cells in sub-G0-G1 phase, ROS production, PS externalization and DNA fragmentation (TUNEL assay). CBD also inhibited intracellular amastigote proliferation (IC50 14.06 μg ml-1) independent of NO production. The in vivo protection achieved was 80.91% (liver) and 82.92% (spleen) in mice and 75.61% (liver) and 78.93% (spleen) in hamsters indicating its profound therapeutic efficacy. CBD exhibited direct antileishmanial activity, as it did not specifically induce a T helper type (Th)-1-polarized mileu in cured hosts. This was evidenced by insignificant modulation of NO production, lymphoproliferation, DTH (delayed type hypersensitivity), serum IgG2a and IgG1 levels and production of Th2 cytokines (IL-4 and IL-10) along with restoration of pro-inflammatory Th1 cytokines (INF-γ, IL-12p70) to the normal range. CBD was devoid of any toxicity in vitro as well as in vivo. The chemical constituents, cinnamaldehyde and its derivatives present in CBD may have imparted the observed antileishmanial effect. Conclusions Our study highlights the profound antileishmanial efficacy of C. cassia bark DCM fraction and merits its further exploration as a source of safe and effective antieishmanial compounds.